2020
DOI: 10.1016/j.heliyon.2020.e05342
|View full text |Cite
|
Sign up to set email alerts
|

Sesaminol prevents Parkinson's disease by activating the Nrf2-ARE signaling pathway

Abstract: Parkinson's disease (PD) is a neurodegenerative disease caused by the degeneration of substantia nigra neurons due to oxidative stress. Sesaminol has strong antioxidant and anti-cancer effects. We investigated the preventive effect on PD as a new physiological action of sesaminol produced from sesaminol glycoside using in vitro and in vivo PD models. To prepare an in vitro PD model, 6-hydroxydopamine (6-OHDA) was added to human neuroblastoma (SH-SY5Y cells). The viability of SH-SY5Y cells decreased dose-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Sesaminol is one type of sesame lignan compound commonly found in sesame seeds and well known for its strong antioxidant and anticancer properties (Miyahara et al, 2001;Watanabe et al, 2017). Using in vitro and in vivo models, Kaji et al (2020) reported the preventive effect of sesaminol on a neurodegenerative disease named as Parkinson's disease (PD). Sesamolin, the second major lignan, found in sesame oil has been regarded as a natural therapeutic agent because of its various therapeutic properties (Michailidis et al, 2019).…”
Section: Compoundmentioning
confidence: 99%
“…Sesaminol is one type of sesame lignan compound commonly found in sesame seeds and well known for its strong antioxidant and anticancer properties (Miyahara et al, 2001;Watanabe et al, 2017). Using in vitro and in vivo models, Kaji et al (2020) reported the preventive effect of sesaminol on a neurodegenerative disease named as Parkinson's disease (PD). Sesamolin, the second major lignan, found in sesame oil has been regarded as a natural therapeutic agent because of its various therapeutic properties (Michailidis et al, 2019).…”
Section: Compoundmentioning
confidence: 99%
“…Both polyphenols showed improved binding affinity at the binding interface of the BA.3 SGp RBD–ACE2 complex due to the multiple interactions with residues such as His14, Glu17, Arg373, and Lys333. Medicinally, sesaminol showed powerful antioxidant and anticancer properties, as well as the ability to prevent Parkinson's disease by activating the Nrf2–ARE signaling pathway 53 . Further, the molecular docking results of the standard drug chloroquine at the SGp RBDs of BA.1, BA.2, and BA.3 with minimum binding energies of −4.7, −4.9, and −4.4 kcal/mol, respectively, were also compared with the screened polyphenols, 16 which clearly supported the importance of polyphenols in suppressing the host–pathogen mediation of SARS‐CoV‐2 by obstructing the interaction between Omicron SGp RBD and hACE2.…”
Section: Resultsmentioning
confidence: 99%
“…Many compounds with known neuroprotective effects have shown to exert their actions through the activation of the NRF2 pathway ( Table 1 ) [ 207 , 208 , 209 ] and chemical screening used to discover new cytoprotective drugs show that their effect is mediated by the NRF2 pathway. Some screening assays have been designed to find NRF2 activators [ 128 , 210 ] or modifying known NRF2 activators, such as sulforaphane [ 211 ], flavonoids [ 212 ], or chalcones [ 213 ], among others, to provide therapeutic effects in cellular models of PD [ 214 , 215 ].…”
Section: Therapeutic Approaches Using Nrf2 For Neuroprotectionmentioning
confidence: 99%